THE IIORPHOLOGICAL STRUCTURE OF THE IIIPERATIVE STEIl IN AIIHARIC - Alemayehu, Haile (The Ethiopian Journal of Education, 2025)
The imperative stem in Amharic may be identified by its selection of a second person subject and by its unique morphological structure. This paper attempts to identify the nature of its core template. In the description of the morphological structure of the imperative stem, a nonlinear model developed in McCarthy (1979, 1981) where the consonantal and vocalic melodies are represented on separate tiers, is adopted. The CV tier is considered to represent an abstract timing slot. The consonantal and vocalic melodies are associated with the relevant unit in the CV tier by the principle of left-to-right association. The Amharic imperative stem is assumed to have a template CCVC for Type A and CVCCC for the Type B and Quadrilateral stems. Epenthesis vowel insertion applies on these basic structures in orders to produce pronounceable (surface) forms. The vowel-insertion rule is motivated by a universal process which related segments within a word with the syllable structure of the language.